Investigating the Pharmacological Mechanisms of SheXiang XinTongNing Against Coronary Heart Disease Based on Network Pharmacology and Experimental Evaluation - Jia, Li-ying; Cao, Gui-yun; Li, Jia; Gan, Lu; Li, Jin-xin; Lan, Xin-yi; Meng, Zhao-qing; He, Xin; Zhang, Chun-feng; Wang, Chong-Zhi; Yuan, Chun-Su (Frontiers in Pharmacology, 2021)
SheXiang XinTongNing(XTN), which is composed of six traditional Chinese herbs, is a commercially available Chinese patent medicine that has been widely used as the treatment of coronary heart disease (CHD). Its mechanisms against coronary heart disease, however, remain largely unknown. This study aimed to investigate the pharmacological mechanisms of XTN against CHD via network pharmacology and experimental evaluation. In this study, GO enrichment and KEGG pathway enrichment were firstly performed for acquiring the potentially active constituents of XTN, the candidate targets related to coronary heart disease, the drug-components-targets network as well as the protein-protein interaction network and further predicting the mechanisms of XTN against coronary heart disease. Subsequently, a series of in vitro experiments, specifically MTT assay, flow cytometry and Real-time quantitative polymerase chain reaction analysis, and a succession of in vivo experiments, including Tunel staining and immunohistochemical staining were conducted for further verification. Results showed that Bcl-2, IGF1, CASP3 were the key candidate targets which significantly associated with multiple pathways, namely PI3K-Akt signaling pathway and MAPK signaling pathway. It indicated that the potential mechanism of XTN against CHD may be predominantly associated with cell apoptosis. The in vitro experimental results showed that XTN treatment remarkably decreased the apoptotic rate and Bax/Bcl-2 ratio of H9c2 cells. Histological results confirmed that XTN not only effectively alleviated oxidative damage caused by myocardial ischemia but inhibited cell apoptosis. Given the above, through the combined utilization of virtual screening and experimental verification, the findings suggest that XTN makes a significant contribution in protecting the heart from oxidative stress via regulating apoptosis pathways, which lays the foundations and offers an innovative idea for future research.